Preparation and evaluation of a novel biodegradable long-acting intravitreal implant containing ligustrazine for the treatment of proliferative vitreoretinopathy. (31st December 2014) - Zhang, Xuemei; Wei, Junhua; Ma, Pengkai; Mu, Hongjie; Wang, Aiping; Zhang, Leiming; Wu, Zimei; Sun, Kaoxiang
Abstract: Objectives: It is challenging to deliver the therapeutic drug effectively to the posterior ocular disease location with optimized exposure and long-term effects when treating proliferative vitreoretinopathy (PVR). The objective of this study is to develop a novel biodegradable and long-acting ocular implant for PVR therapy with ligustrazine as the active ingredient. Methods: The ligustrazine implants were prepared with poly(DL-lactide-co-glycolide) using a hot-melting extrusion. The physicochemical properties of the implants were characterized. The effectiveness of the selected ligustrazine implants was evaluated in a PVR rabbit model. Furthermore, the in-vitro drug release profile and pharmacokinetics were compared, and in-vitro/in-vivo correlations were evaluated. Key findings: The optimal implants had an ideal zero-order in-vitro drug release profile, which was correlated with the in-vivo drug absorption fraction in the vitreous bodies of the rabbits. The sustained-release ligustrazine implants significantly reduced the development of PVR in the animal model. Conclusions: Ligustrazine implants can be used to treat posterior ocular disease in rabbit animal models, and it provides more choices for medical research on posterior ocular disease.